2012
DOI: 10.1021/bm300582s
|View full text |Cite
|
Sign up to set email alerts
|

Dialkyl Phosphate-Related Ionic Liquids as Selective Solvents for Xylan

Abstract: Herein we describe a possibility of selective dissolution of xylan, the most important type of hemicellulose, from Eucalyptus globulus kraft pulp using ionic liquids (ILs). On the basis of the IL 1-butyl-3-methylimidazolium dimethyl phosphate, which is well-known to dissolve pulp, the phosphate anion was modified by substituting one oxygen atom for sulfur and selenium, respectively. This alteration reduces the hydrogen bond basicity of the IL and therefore prevents dissolution of cellulose fibers, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 68 publications
(153 reference statements)
3
29
0
Order By: Relevance
“…We note that both phosphoroselenolate diesters (4a and 4b) appeared stable towards both oxidation and hydrolysis by 31 P NMR during these manipulations and no degradation of 4b was observed upon storage in D2O for 12 hours under ambient conditions. More extensive investigations of the lability of internucleotide phosphoroselenolates are ongoing.Stec and co-workers had previously described the synthesis of 3b and both the chemical shifts and coupling constants (δP = 21.27 28 and an earlier study of the relationship of the magnitude of the P-Se coupling constant and bond order 29 supports our assignment. In summary, we have demonstrated that the reactions of a nucleoside H-phosphonate diester with alkyl selenocyanates in the presence of a mild base and neutral silylating agent proceeded rapidly and cleanly to give the corresponding phosphoroselenolate triesters.…”
supporting
confidence: 74%
“…We note that both phosphoroselenolate diesters (4a and 4b) appeared stable towards both oxidation and hydrolysis by 31 P NMR during these manipulations and no degradation of 4b was observed upon storage in D2O for 12 hours under ambient conditions. More extensive investigations of the lability of internucleotide phosphoroselenolates are ongoing.Stec and co-workers had previously described the synthesis of 3b and both the chemical shifts and coupling constants (δP = 21.27 28 and an earlier study of the relationship of the magnitude of the P-Se coupling constant and bond order 29 supports our assignment. In summary, we have demonstrated that the reactions of a nucleoside H-phosphonate diester with alkyl selenocyanates in the presence of a mild base and neutral silylating agent proceeded rapidly and cleanly to give the corresponding phosphoroselenolate triesters.…”
supporting
confidence: 74%
“…Dialkylimidazolium chlorides usually have a β parameter of just above 0.80 and bromides around 0.75. Ionic liquids that have similar β parameters but different anions, such as [C 4 84 do not dissolve cellulose. This suggests that, around the cut-off, secondary effects such as anion size and geometry play a role and may decide whether an ionic liquid solubilises cellulose or not.…”
Section: The Solubility Of Cellulose In Ionic Liquidsmentioning
confidence: 99%
“…Very recently, Froschauer et al demonstrated ILs with selenium-and sulfur-substituted dialkyl phosphate anions that can selectively dissolve components of hemicellulose over cellulose; tests with lignin were not noted. [60] Casas et al recently performed the first simulations aimed at exploring lignin solvation in ILs, using glucose and pinoresinol as models for glucose and lignin respectively. [22] Using COSMO-RS (Conductor-like Screening Model for Real Solvents) as a prediction tool, the excess enthalpy for these models was calculated in four different ILs.…”
Section: Dissolution Of Lignocellulosic Biomass With Ionic Liquidsmentioning
confidence: 99%